Pengaruh Pertumbuhan Penjualan Dan Intensitas Modal Terhadap Penghindaran Pajak Pada Perusahaan Sektor Real Estate Yang Terdaftar Di BEI Tahun 2022-2024 - Vincent Salim; Siti Khairani (Politeknik Negeri Padang, 2026)
The objective of this research is to analyze the impact of sales growth and capital intensity on tax avoidance behavior in IDX-listed real estate firms throughout the years 2022 to 2024. Employing a quantitative methodology, employs multiple linear regression analysis to evaluate the correlation between tax avoidance as the dependent factor and two independent predictors which is sales growth and capital intensity.. Secondary data was gathered from the official annual financial statements of property and real estate firms publicly traded on the IDX. Empirical findings indicate that neither the growth in sales nor the level of capital intensity exerts a statistically significant effect on the tax avoidance behaviors of the sampled companies. These results are inconsistent with the agency theory used in this study, which explains that within a company there will be differences in interests between the principal as shareholder and the agent as management, which will cause each party to do things that benefit their own interests..